Use of prophylactic antivirals and care home characteristics associated with influenza in care homes with confirmed outbreaks. (December 2019) - Shah, A.; Harries, A.D.; Cleary, P.; McGivern, M.; Ghebrehewet, S.
Abstract: Objectives: To assess the association of antiviral prophylaxis and care home characteristics with the spread and severity of influenza-like illness in care homes with influenza outbreaks in North West England in the 2017/2018 influenza season. Study design: This is a retrospective observational study. Methods: Routinely collected outbreak surveillance data reported to Public Health England were extracted from health protection electronic records. Data included use of antiviral prophylaxis, influenza-like illness or confirmed influenza, hospital admissions and deaths. Care home characteristics were obtained from the Care Quality Commission website. Single variable analysis and multivariable logistic regression were used to examine associations between care home characteristics, antiviral prophylaxis and influenza-related outcomes. Results: In the 109 homes, there were 3498 residents; of whom, 855 (24%) developed an influenza-like illness. Antiviral prophylaxis was given to residents of 67 of the 109 care homes with outbreaks (61%). A significantly higher attack rate was observed among residents of homes given antiviral prophylaxis (27%) than among residents of homes not given antivirals (20%) ( P  < 0.001). Significantly more deaths occurred in homes for people with learning disabilities and homes that received antiviral prophylaxis ( P  < 0.001). Conclusions: In homes given antiviral prophylaxis, there were a higher number of residents with influenza-like illness and deaths. To improve our understanding of the impact of antiviral prophylaxis use in real life, enhanced and timely data collection is needed for identification of temporal associations between exposure and administration of antiviral prophylaxis. Consideration needs also to be given to ensure people with learning disabilities are protected through the seasonal influenza vaccine and timely antiviral prophylaxis when appropriate. Highlights: The study used routinely collected outbreak surveillance data from care homes. Influenza-like illness was more common in care homes where residents were given antiviral prophylaxis. Small homes and homes for people with learning disabilities were also risk factors. Homes with large numbers of residents had lower rates of influenza-like illness.